Kebijakan Pemerintah dalam Meningkatkan Prestasi Atlit Nasional - Harahap, Insan Harapan (Journal of Entrepreneurship, Management and Industry (JEMI), 2018)
Sports is an activity to ensure physical health for each individual. Furthermore, sports have prestige, special value, pride, and pride. Each country must send its national athletes to compete with other athletes in international sports competitions. Achievements measured by the high number of gold medals are the main goals that must be achieved by every national athlete, especially Indonesian athletes. So that various efforts must be made to win in every sport both nationally and internationally. The history of the achievements of Indonesian national athletes experiences tidal dynamics in various sports. In fostering athletes, the government has issued several policies, such as Law No. 3 of 2005 concerning National Sports System (UUSKN) and Law No. 40 of 2009 concerning Youth. In its implementation, several supporting and inhibiting factors were found in improving the achievement of national athletes. On this basis, the Indonesian government must respond wisely as a step to improve the performance of national athletes.